Development of a pilot-scale web-based inventory management system foe lab equipment and consumables - Karim, A.N. Mustafizul; Saad, Mohd Fadli (2009)
A proper management of inventory items can bring in significant benefit to any organization. With the advancement of communication system through internet and intranet, its scope is expanding rapidly in the form of web-based system. A web based inventory management system can bring exceptional value to an organization. As an organization grows, it is inevitable to deal with a lot of paper-based records for each transaction, thus requiring a lot of storage. Additionally, strict control of inventory with frequent cycle counting and high record accuracy is becoming imperative to survive in this competitive world. A web-based inventory system, as an alternative to conventional system, provides a platform where records can be archived and updated digitally, thus reducing filing activity at the end of each term and providing a scope of frequent counting with higher record accuracy. Another significant advantage is that a web based system can be accessed by authorized person anywhere and anytime. As a result, a manager should be a happier person if he can feel more 'in control' of what he manages. There has been a common perception that an inventory model is developed mostly in the context of manufacturing, wholesale, and retail sectors. Now with the advantages of the web based system, application of inventory management has crossed the common boundary. The pilot-scale research project was undertaken to study the scope of web based inventory system for managing laboratories of engineering program at a higher learning institute. Relevant data and information from few laboratories were gathered including the list of current inventory items. A web-based inventory management system for the laboratory inventory has been developed which could be used to check the current status of raw materials, consumables and machinery available, reveal the pattern of the need of materials in the various laboratories, identify the critical parts and equipment, and current stock level. A built-in function in the system can be used for planning in the context of determining the order quantity, reorder quantity and lead time.